2017
DOI: 10.1371/journal.pone.0177160
|View full text |Cite
|
Sign up to set email alerts
|

miR-27a and miR-449b polymorphisms associated with a risk of idiopathic recurrent pregnancy loss

Abstract: ObjectiveMicroRNAs (miRNAs) regulate gene expression during the peri-implantation period. The purpose of this study was to investigate whether genetic polymorphisms in the four miRNAs associated with fetal or placental development play roles in the development of idiopathic recurrent pregnancy loss (RPL) in Korean females.Study designA case-control study involving 225 controls and 387 women with at least two consecutively recurrent pregnancy losses between 1999 and 2012 was performed. The genotypes of the four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 32 publications
5
31
0
Order By: Relevance
“…Some DE miRNAs identified in our study play a significant role in pregnancy loss. The miR-27a polymorphism, for example, is significantly associated with pregnancy loss in humans [52]. Consistent with our findings, Wessels et al identified miR-323 and miR-27a as potentially involved in spontaneous embryo loss in pigs [51].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Some DE miRNAs identified in our study play a significant role in pregnancy loss. The miR-27a polymorphism, for example, is significantly associated with pregnancy loss in humans [52]. Consistent with our findings, Wessels et al identified miR-323 and miR-27a as potentially involved in spontaneous embryo loss in pigs [51].…”
Section: Discussionsupporting
confidence: 92%
“…We also identified 14, 36, 57, and 43 DE miRNAs (p-value < 0.05) in the four comparisons described above ( Supplementary Material Table S9). Among these, miR-19a [50], miR-323 [51], miR-27a [51,52], miR-30a-5p [53] may be involved in fetal loss during pregnancy. Venn diagrams showing the differentially expressed genes and miRNAs from the four groups are presented in Figure 1A (mRNAs) and Figure 1B Table S9).…”
Section: Identifying Differentially Expressed Mrnas and Mirnasmentioning
confidence: 99%
“…The authors suggested that miRNAs represent a potential target for clinical sepsis research and treatment. 44 MiR-124-3p was found downregulated in endometrial cancers and recently it has been demonstrated that modified exosomes could efficiently deliver miR-124-3p to the brain and that miRNAs are able to protect against ischemic injury by robust cortical neurogenesis. 43 Finally, a recent paper reported that miR-27a-3p polymorphisms are associated with a risk of idiopathic recurrent pregnancy loss.…”
Section: Discussionmentioning
confidence: 99%
“…43 Finally, a recent paper reported that miR-27a-3p polymorphisms are associated with a risk of idiopathic recurrent pregnancy loss. 44 MiR-124-3p was found downregulated in endometrial cancers and recently it has been demonstrated that modified exosomes could efficiently deliver miR-124-3p to the brain and that miRNAs are able to protect against ischemic injury by robust cortical neurogenesis. 45,46 We found the downregulation of IGF1 and IL11 and demonstrated the anticorrelation between miR-27a-3p and IGF1 (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated an association between genetic variants and the risk of RSA (27)(28)(29)(30). VEGF is among the established regulators of angiogenesis during pregnancy and has been associated with RSA (31,32).…”
Section: Resultsmentioning
confidence: 99%